Matters of projects classification and ranking by applicable technical systems - Чимшир, Валентин Иванович (Eastern-European Journal of Enterprise Technologies, 2013)
Technical systems application extent analysis in implementation of projects of various types has been carried on. Classification feature and its parameters have been identified and ranking of projects has been carried on in accordance with classification feature. As regards projects of social and technological orientation being implemented all the technical systems are proposed to be grouped into three subclasses: universal, specialized and special. Detailed description of classified projects types is provided subject to four criteria: project aim, project budget, project results stability and scale, project results social significance. A diagram of correlation between types of projects and technical systems has been suggested.